Culinária como um recurso didático para o ensino de biomoléculas: carboidratos, lipídios e proteínas - Freitas, Josilene de Souza (2024)
In pedagogical practice, one of the greatest challenges for teachers is to link theory and practice in a way that makes the content as engaging as possible for students. At the same time, making them protagonists of their learning through inquiry-based teaching is a necessity whose difficulty is significant - especially in the post-pandemic return - and even more so when it comes to biochemistry content, considered difficult to learn. Literature points out that practical laboratory classes can minimize such difficulties, however, data from the 2022 School Census indicate that science laboratories are present in only 38.8% of brazilians public high schools, which exacerbates the teaching process and implies the need for teachers to develop new strategies that aim for effective student learning. In this context, the present work aimed to present the teaching of biomolecules linked to cooking, proposing practical classes that integrated the content addressed in the classroom with effective student practice, where students had the opportunity to visualize the content in a playful way, through inquiry-based teaching. This alternative didactic approach to traditional practice permeated our questioning about whether such an approach is indeed more constructive than the traditional one. Therefore, the work had a qualitative character and was developed in a class of 27 students from the 1st grade of high school at the Carlota Barreira State School of Elementary and Secondary Education, located in the city of Areia – PB. The pedagogical strategies were based on investigative teaching activities and aimed at improving the teaching-learning of biomolecules (carbohydrates, lipids, and proteins) in high school - when compared to traditional teaching, and student protagonism. Thus, the school spaces used were the classroom itself and the school kitchen, where the activities based on the proposed recipes were developed. The results of this work were evaluated through continuous assessment throughout the process and the results obtained through questionnaires. Analyzing the results obtained through the developed methodological path and the applied pedagogical practices, it can be concluded that the intended results - such as increased student protagonism in classes, bringing classroom content closer to reality, and linking theory and practice through culinary experimentation - were achieved. The use of food as a learning tool offered a tangible connection between theory and practice. As a product and result of this work, a didactic guide was produced that, by presenting biochemistry teaching linked to culinary practice, seeks to be an additional aid to high school Biology teachers.